THE ROLE OF OMBUDSMAN IN ENFORCING THE WHISTLEBLOWING SYSTEM IN INDONESIA: PERANAN OMBUDSMAN DALAM PENEGAKAN SISTEM PELAPORAN PELANGGARAN DI INDONESIA - Maulana, Nietan Bagas; Hanum, Cholida (Constitutional Law Society, 2025)
Ombudsman is a part of an auxiliary state institution or often referred to as an auxiliary state organ in Indonesia. One of the duties and functions of the Ombudsman institution is to supervise the running of the public service system in Indonesia, the presence of this institution is expected to be able to improve the protection of people's rights in order to obtain public services, justice, and good welfare. The ombudsman institution has the authority to monitor and examine various reports based on complaints given by the public regarding the state administration system through the whistleblowing system that the Ombudsman of the Republic of Indonesia has. For the duties and functions of this Ombudsman institution which is considered strategic, which has been reviewed from the perspective of theory (auxiliary state organs) and the theory of authority, it is hoped that this institution can maintain stability between various other institutions in Indonesia. The method used in this study is doctrinal legal research and normative juridical research approach because this research takes a legal issue as a form of normative system such as laws and regulations. The results of the research that have been carried out show that the Ombudsman institution is considered to have a very crucial role in supervising all forms of the government public service implementation system in Indonesia through the whistleblowing system mechanism, then it needs to be strengthened again regarding the position of the Ombudsman as an auxiliary state organ and its authority to hold on to the products that can be produced by this institution only in the form of recommendations, not sanctions that can be binding.